Evaluation of two histological classifications for actinic keratoses – PRO classification scored highest inter‐rater reliability. (3rd April 2019) - Schmitz, L.; Gupta, G.; Stücker, M.; Doerler, M.; Gambichler, T.; Welzel, J.; Szeimies, R.M.; Bierhoff, E.; Stockfleth, E.; Dirschka, T.
Abstract: Background: Actinic keratoses (AKs) can histologically be classified by the extent of atypical keratinocytes throughout the epidermis or their pattern of basal proliferation. Currently, no data on the inter‐rater reliability of both scores is available. Objective: To evaluate the inter‐rater reliability of the two classification schemes; histological grade (AK I–III) and basal proliferation (PRO I–III). Methods: Histological images of 54 AKs were classified by 21 independent dermatopathologists with regard to basal proliferation (PRO I–III), histological grade (AK I–III) and assumed risk of progression into invasive carcinoma. Results: Overall, of the 54 AKs 16.7% (9/54) were classified as AK I, 66.7% (36/54) as AK II, and 16.7% (9/54) as AK III. With regards to basal growth pattern, 25.9% (14/54) were classified as PRO I, 42.6% (23/54) as PRO II, and 31.5% (17/54) as PRO III. We observed a highly significant inter‐rater reliability for PRO‐grading ( P < 0.001) which was higher than for AK‐grading (Kendall's W coefficient: AK = 0.488 vs. PRO = 0.793). We found substantial agreement for assumed progression risk for AKs with worsening basal proliferation ( k = 0.759) compared to moderate agreement ( k = 0.563) for different AK‐gradings. Conclusions: Histological classification of basal growth pattern (PRO) showed higher inter‐rater reliability compared to the established classification of atypical keratinocytes throughout epidermal layers. Moreover, experienced dermatopathologists considered basal proliferation to be more important in terms of progression risk than upwards directed growth patterns. It should be considered to classify AKs according to their basal proliferation pattern (PRO I–III). Abstract : Linked Commentary: F. Rongioletti. J Eur Acad Dermatol Venereol 2019;33 : 983–984.https://doi.org/10.1111/jdv.15649 .